Prawo dzieci do edukacji a jakość nauczania w Afryce Subsaharyjskiej na przykładzie Madagaskaru - Lendzion, Kinga (Annales Missiologici Posnanienses, 2016)
In 2003 Madagascar joined the UNESCO “Education for All” programme. The primary objective of the programme is to improve accessibility to and the quality of the education system. Although there has been progress in achieving universal primary education, this progress has not been accompanied by the necessary safeguards for ensuring quality of education. According to the UNESCO report “Éducation pour tous. Madagascar 2015" only 79% the Malagasy children who started school went on to complete their primary education. The PASEC (Program on the Analysis of Education Systems) report also shows the low quality of education – children repeating school years together with low educational outcomes in Mathematics and French. This poor quality of education is undoubtedly in violation of the rights of children to their individual development. This article attempts to answer the question about the causes of the low quality of education in Madagascar. According to the author it’s important to note that apart from poverty and child labour the low professional qualifications of teachers is also a contributory factor.